Fox and the jumping contest - Tabor, Corey R. (New York : HarperCollins, 2016)
"Fox really, really wants to win the jumping contest. He knows just where he'll put that first-place trophy. The only problemFox is not a very good jumper. But he is a very good schemer. . . .The irrepressible fox (sort of) wins and (sort of) gets his comeuppance in this hilarious modern-day trickster tale"--Jacket flap.
Ages 4-8.
A/R 2.3 lower grades 0.5 points.
Keywords: Foxes -- Juvenile fiction; Animal jumping -- Juvenile fiction; Tricksters -- Juvenile fiction; Picture books; Contests -- Fiction; Jumping -- Fiction; Animals -- Fiction; Foxes. -- Juvenile fiction; Foxes. -- Fiction; Contests -- Juvenile fiction; JUVENILE FICTION -- Animals -- Foxes; JUVENILE FICTION -- Fairy Tales & Folklore -- Adaptations; JUVENILE FICTION -- Humorous Stories; Picture books; Animal jumping; Foxes; Tricksters; Animal jumping -- Fiction; Tricksters -- Fiction; Foxes -- Fiction; Picture books; Fiction; Juvenile works; Picture books; Picture books for children; Picture books for children